Pilot study of hepatic intraarterial fotemustine chemotherapy for liver metastases from uveal melanoma: a single-center experience with seven patients - Egerer, Gerlinde; Lehnert, Thomas; Max, Regina; Näher, Helmut; Keilholz, Ulrich; Ho, Anthony Dick (International journal of clinical oncology, 2001)
Background. Uveal melanoma is characterized by a high frequency of hepatic metastases. For patients with liver metastases, who have a median survival of 5 to 7 months, surgery and systemic conventional chemotherapy have little to offer.
Gesehen am 21.12.2021